Evaluation of the protection of a vectorized vaccine against Gumboro disease under controlled conditions in commercial laying pullets - Lavado A., Nicol (2018)
The protection conferred by a vaccination programme against Gumboro disease was evaluated in commercial laying pullets vaccinated with a trivalent vectorized vaccine applied at the first day of age via eye-drop. One hundred pullets distributed in two groups of 50 chicks were used. Group A vaccinated with the trivalent vaccine and group B not vaccinated. At 35 days of age the birds were challenged with the classic strain F 52/70 of the Gumboro virus via ocular route. Mortality, clinical signs, macro and microscopic bursal lesions and Bursal index before and after the challenge were evaluated as protection indicators. In addition, the immune response was evaluated on day 1, 35 and 49 of age using the ELISA test and productive parameters of both groups were also compared. Birds of the unvaccinated group had 33.3% of clinical Gumboro mortality and clinical signs (diarrhea and depression) and macro and microscopic lesions more severe than those of the vaccinated group, and vaccinated birds did not show mortality and were fully recovered of clinical signs 10 days after the challenge. The values of the Bursal index of birds of group B indicated bursal atrophy at 6 and 14 days post challenge, but not those of group A. On day 35 (the day of the challenge), the birds of group A showed low seroconversion of maternal antibodies while group B no antibodies were detected (p<0.05). The vaccinated group obtained greater body weight, and better feed conversion and uniformity in relation to the unvaccinated group (p<0.05). It is concluded that the vaccination of laying pullets with trivalent vectorized vaccine at the first day of age induces efficient protection against the clinical form of Gumboro disease.